The establishment of a legal framework for the sustainable development of renewable energy in Nigeria - Yamusa, Shehu Usman, II (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
Nigeria has abundance of untapped sources of energy and, at the same time, it suffers from inadequacy of fossil fuel for the generation of electricity. Its energy generation values are diminishing very much and very fast. Therefore, slowing development will not bring foreign ideas and cultures that appear to be suitable for the sustainable development in renewable energy. The National Energy Policy and Action Plan need to be reviewed since 2007. Energy generation is barely very low with only 4,000 MW at the moment. The environmental issues in the oil production areas are alarming for more than 50 years as gas flaring is still on in the country. Therefore, there is a need for viable reform in the energy sector to bring about the development of sustainable energy through the diversification of energy sources. This work has proposed a viable framework that will establish a legal and institutional framework for the sustainable development of renewable energy in Nigeria. In achieving the set objective, this research adopts the doctrinal legal research methods, i.e. qualitative research. Primary and secondary materials have been examined to see how Nigeria with abundant sources of energy can also generate electricity in the country for sustainable development. Meanwhile, Malaysia, Netherlands and India are closely studied in the areas where Nigeria can adopt to improve it energy generation. Finally, this research discusses relevant laws and policies relating to planning, and energy generation for the diversification of energy sources that will bring sustainable energy in the country